Credit Attribution for Public Service Providers and Their Employees: Implications from Contracting Out - Suzanne Leland; Jaclyn Piatak; Zachary Mohr (The American Review of Public Administration, 2026)
Both government and government employees alike face negativity bias, but could conveying the exemplary work of public service help address declining public trust and engagement? While scholarly research has examined how the public assigns blame when the government or a contractor falls short, far less attention has been paid to the positive side. How is credit assigned to employees and agencies when they go above and beyond what is required in their jobs? This research addresses this gap through a vignette survey experiment, which is used to determine how contracting influences credit given to the service provider and the individual employee across levels of government –federal, state, and local. The results reveal that credit is more likely to be given to third-party providers than the government directly providing the service. However, at the individual employee level, the public prefers to give credit to public employees, especially at the federal government level, when outstanding work occurs. Findings have implications for contracting, performance, and accountability, where perhaps sharing more positive stories of public service can foster more positive public views.